The Role of Foundation Grantmakers in Responding to Community Aging: John T. Gorman Foundation - Cipollone, Tony (Maine Policy Review, 2015)
Tony Cipollone of the John T. Gorman Foundation responds to a series of questions about the role of grantmakers in responding to community aging.
Keywords: aging; Maine; grantmakers; philanthropy